Observer Performance in the Use of Digital and Optical Microscopy for the Interpretation of Tissue-Based Biomarkers - Marios A. Gavrielides; Catherine Conway; Neil O’Flaherty; Brandon D. Gallas; Stephen M. Hewitt (Analytical Cellular Pathology)
Background. We conducted a validation study of digital pathology for the quantitative assessment of tissue-based biomarkers with immunohistochemistry. Objective. To examine observer agreement as a function of viewing modality (digital versus optical microscopy), whole slide versus tissue microarray (TMA) review, biomarker type (HER2 incorporating membranous staining and Ki-67 with nuclear staining), and data type (continuous and categorical). Methods. Eight pathologists reviewed 50 breast cancer whole slides (25 stained with HER2 and 25 with Ki-67) and 2 TMAs (1 stained with HER2, 1 with Ki-67, each containing 97 cores), using digital and optical microscopy. Results. Results showed relatively high overall interobserver and intermodality agreement, with different patterns specific to biomarker type. For HER2, there was better interobserver agreement for optical compared to digital microscopy for whole slides as well as better interobserver and intermodality agreement for TMAs. For Ki-67, those patterns were not observed. Conclusions. The differences in agreement patterns when examining different biomarkers and different scoring methods and reviewing whole slides compared to TMA stress the need for validation studies focused on specific pathology tasks to eliminate sources of variability that might dilute findings. The statistical uncertainty observed in our analyses calls for adequate sampling for each individual task rather than pooling cases.